Integrating safety climate and safety performance through internal ties strength, risk perception and job burnout: Proactive approaches in organizational safety management - Muhammad, Ibrahim; Abdul Aziz, Mohd Azoddein; Muhammad Fakhrul, Yusuf; Rashidah, Ramle (GBMR, 2025)
Purpose: This study explores the integration of safety climate and safety performance within organizations, emphasizing the roles of internal ties strength, risk perception, and job burnout. Strong internal ties among employees are found to foster a cohesive and positive safety climate, leading to improved safety performance as employees are more likely to adhere to safety protocols and engage in safe behaviors when supported and connected. Risk perception is identified as crucial in shaping safety behaviors and outcomes. The research underscores the importance of effective communication about risks to foster a shared understanding of safety priorities among employees. Additionally, job burnout is addressed as a significant factor that negatively impacts safety performance, leading to decreased vigilance and reduced compliance with safety procedures. Addressing job burnout through supportive work environments and stress management initiatives is deemed essential for maintaining high safety standards. This study proposes a comprehensive framework for enhancing safety climate and performance by integrating these elements: internal ties strengths, risk perception, and job burnout. Design/methodology/approach: This study employs a quantitative, cross-sectional design to examine the relationships between safety climate, safety performance, internal ties, risk perception, and job burnout within organizations, specifically focusing on the Malaysian petrochemical industry. Data is collected via surveys distributed to employees, using standardized and validated scales to measure key constructs: internal ties strength, risk perception, job burnout, safety climate, and safety performance. The analysis uses structural equation modeling (SEM) to test the proposed conceptual framework, exploring direct and indirect relationships among variables. Descriptive statistics, correlation analysis, and mediation analysis are conducted to understand the interactions between internal ties, risk perception, burnout, and safety outcomes. Reliability is ensured through Cronbach’s alpha, while confirmatory factor analysis (CFA) validates the measurement tools. The study is grounded in safety climate theory and conservation of resources (COR) theory, offering a robust theoretical foundation. Based on the results, practical interventions are proposed to strengthen internal ties, improve risk perception management, and mitigate job burnout. These interventions aim to foster a proactive safety climate and enhance overall safety performance within organizations by focusing on strategic relationship-building, communication, and employee well-being.